Antimicrobial potential of silver nanoparticles biosynthesized using aerial yam bulbils for control of selected phytopathogens. (14th December 2021) - Singh, Rita; Patade, Vikas Y.; Sanchita,; Singh, Antaryami
Abstract: Silver nanoparticles as antimicrobial agent have vast potential in agriculture for the protection of plants from diseases and increasing crop productivity. In this study, the bulbils of aerial yam ( Dioscorea bulbifera L.) were investigated for their potential for biosynthesis of silver nanoparticles. Variation in the absorption spectra of silver nanoparticles synthesized using different concentrations of 10 to 50% (v/v) of plant extract was observed. Phytochemical analysis of aerial yam bulbils revealed high content of flavonoid (4.06 ± 0.44 mg/g), phenols (3.36 ± 0.20 mg/g) and tannins (12.42 ± 0.22 mg/g) with potential role in the bioreduction process. Highest inhibition (98-100%) was recorded against Fusarium oxysporum and Colletotrichum gloeosporioides with 100 ppm silver nanoparticles. The inhibition zone against Bacillus sp. and Enterobacter cloacae ranged from 6.00 ± 0.41 to 11.00 ± 0.87 mm at 100 ppm concentration indicating antibacterial efficacy of biosynthesized silver nanoparticles. Silver nanoparticles biosynthesized using 20% (v/v) extract at higher temperature demonstrated the most effective inhibition of plant pathogenic fungi and bacteria.